2006
DOI: 10.1158/0008-5472.can-05-0542
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma Lysis by T Cells Expressing a Human Autoantibody-Based Chimeric Receptor Targeting the Fetal Acetylcholine Receptor

Abstract: Rhabdomyosarcomas are the most frequent malignant soft tissue tumors of childhood; however, because current multimodality treatments fail to improve the poor survival rate of children with metastatic rhabdomyosarcoma, new treatments are required. We previously identified the ;-subunit of the fetal acetylcholine receptor ( fAChR) as a specific cell surface target in rhabdomyosarcoma. Here, we engineered human T lymphocytes to express chimeric receptors composed of the antigen-binding domain of a human anti-fACh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 19 publications
1
32
0
5
Order By: Relevance
“…The expression of the tumor-specific antigens MAGE, GAGE, and BAGE were detected in RMS, and initial efforts showed that RMS cells are able to process MAGE-A proteins and present the resulting peptides to T cells [100]. Based on the high expression level of the fetal type acetycholine receptor (fAChR) by RMS tumors in contrast to the expression of the adult type by mature skeletal muscle, fAChR has been proposed as another candidate target antigen for immunotherapy [101]. As a strategy to bypass the intrinsic immune resistance of RMS cells, T lymphocytes were engineered to express a chimeric receptor consisting of the antigen-binding domain of a human antifAChR antibody combined with the cytoplasmic signaling domain of the human T cell receptor ζ chain.…”
Section: Rms and Tumor Immunitymentioning
confidence: 99%
“…The expression of the tumor-specific antigens MAGE, GAGE, and BAGE were detected in RMS, and initial efforts showed that RMS cells are able to process MAGE-A proteins and present the resulting peptides to T cells [100]. Based on the high expression level of the fetal type acetycholine receptor (fAChR) by RMS tumors in contrast to the expression of the adult type by mature skeletal muscle, fAChR has been proposed as another candidate target antigen for immunotherapy [101]. As a strategy to bypass the intrinsic immune resistance of RMS cells, T lymphocytes were engineered to express a chimeric receptor consisting of the antigen-binding domain of a human antifAChR antibody combined with the cytoplasmic signaling domain of the human T cell receptor ζ chain.…”
Section: Rms and Tumor Immunitymentioning
confidence: 99%
“…Immune therapy may offer such an approach because RMS cells are potentially susceptible to cytolysis by redirected T cells, 14 antigen-independent cytokine-induced killer cells, 29 and activated natural killer cells, 30 although with disappointing low efficacy. Herein, we show that this may be due to, at least in part, inefficient effector cell activation as the result of lack of costimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent, according to the Declaration of Helsinki, was obtained from all patients or their legal guardians, depending on the patients' age. All cases were studied by RT-PCR for fAChR expression 14 and for PAX-FKHR fusion transcript status by the Molecular Biology Laboratory at Olga Hospital (Stuttgart). 24 …”
Section: Biopsy Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown an expansion of receptors against other antigen targets on solid tumors, such as epidermal growth factor receptor vIII on glioblastoma [116], prostate stem cell antigen on prostate cancer [117], fetal acetylcholine receptor on rhabdomyosarcoma [118], and MUC1 on breast cancer cells [17]. In addition, novel, antigenic targets on hematological cancers have been addressed, such as CD38 on non-Hodgkin's lymphoma [119].…”
Section: Discussionmentioning
confidence: 99%